Critical Factors in E-Learning Influencing Student Motivation and Collaboration in Indonesian Higher Education Institution - Yulia Magdalena; Togar Alam Napitupulu (The Winners, 2018)
The purpose of this research was to determine the effect of e-learning and its elements to student motivation and collaboration. This research was conducted in one of Indonesian higher education institutions. A questionnaire was distributed to collect data from students. Data were obtained from 145 active undergraduate students. The statistical method of multiple regression analysis was used for data analysis, using software Statistical Product and Service Solution (SPSS) version 22. Overall, the results of this research indicate that e-learning has a positive impact on student motivation and collaboration. However, it is found that not all elements of e-learning have positive impacts on student motivation and collaboration.